2020
DOI: 10.1111/1759-7714.13299
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming resistance by ALK compound mutation (I1171S + G1269A) after sequential treatment of multiple ALK inhibitors in non‐small cell lung cancer

Abstract: Background Anaplastic lymphoma kinase (ALK) fusion genes are found in 3%–5% of non‐small cell lung cancers (NSCLCs). ALK inhibitors show a very high response rate to ALK‐positive NSCLCs. However, the emergence of acquired resistance is inevitable. In this study, we investigated the drugs for overcoming resistance especially compound mutations after sequential treatment with crizotinib, alectinib, and lorlatinib. Method Next‐generation sequencing (NGS) and Sanger sequencing were performed on a liver biopsy tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…11 Some researchers have reported that tumors with compound mutations such as I1171N with L1196M or I1171N with G1269A are also sensitive to ceritinib. 7,12 There is a study suggesting that epithelial mesenchymal transition (EMT) is associated with resistance to ALK-TKI. 13 Lung adenocarcinoma before ALK-TKI treatment was E-cadherin-positive and vimentin-negative, but it changed to E-cadherin-negative and vimentin-positive during progression after treatment with ALK-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some researchers have reported that tumors with compound mutations such as I1171N with L1196M or I1171N with G1269A are also sensitive to ceritinib. 7,12 There is a study suggesting that epithelial mesenchymal transition (EMT) is associated with resistance to ALK-TKI. 13 Lung adenocarcinoma before ALK-TKI treatment was E-cadherin-positive and vimentin-negative, but it changed to E-cadherin-negative and vimentin-positive during progression after treatment with ALK-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…However, changeable scenarios may emerge such as the case of a patient treated with the sequence of crizotinib-ceritinib-lorlatinib, who developed a post-lorlatinib L1198F mutation, along with the post-crizotinib C1156Y, and surprisingly responded to crizotinib; this double compound mutation C1156Y/ L1198F re-sensitizes patient's tumor to first-generation ALKi (29). Also the I1171S/G1269A mutation, identified in a liver lesion at progression to lorlatinib, turned out to be sensitive to ceritinib and brigatinib and the patient responded to treatment with ceritinib (30).…”
Section: Third Generation Alki (Lorlatinib) and Emergence Of Compound Mutationsmentioning
confidence: 98%
“…D, Patterns of base substitutions identified in our recent studies [19][20][21] that used Ba/F3 models and N-ethyl-N-nitrosourea (ENU) mutagenesis. Secondary mutation data are from following references:: EGFR mutation 6,16,28-30,32,36,39-43,97-109 , ALK fusion [45][46][47][48][49]51,[53][54][55][56][57][110][111][112][113][114][115][116][117] , ROS1 fusion 17,53,59,63,64,[118][119][120][121][122][123] , RET fusion 69,70,[124][125][126] , NTRK fusion 73,75,76,127 , and MET exon 14 skipping 20,21,81,[83][84][85][86]…”
Section: E Xplor Ation Of S Econdary/ Tertiary Mutati On S That C Aus...mentioning
confidence: 99%
“…D, Patterns of base substitutions identified in our recent studies 19‐21 that used Ba/F3 models and N‐ethyl‐N‐nitrosourea (ENU) mutagenesis. Secondary mutation data are from following references:: EGFR mutation 6,16,28‐30,32,36,39‐43,97‐109 , ALK fusion 45‐49,51,53‐57,110‐117 , ROS1 fusion 17,53,59,63,64,118‐123 , RET fusion 69,70,124‐126 , NTRK fusion 73,75,76,127 , and MET exon 14 skipping 20,21,81,83–86,88,89,95,128‐132 . *In RET and NTRK fusions, the resistance mutations that emerged in other type of cancers are also included.…”
Section: Ba/f3 Cells As a Tool To Identify On‐target Acquired Resista...mentioning
confidence: 99%